Methane potential from municipal biowaste: Insights from six communities in Maharashtra, India. (April 2018) - Breitenmoser, Lena; Dhar, Hiya; Gross, Thomas; Bakre, Milan; Huesch, Ragini; Hugi, Christoph; Wintgens, Thomas; Kumar, Rakesh; Kumar, Sunil
Highlights: Empirical data on biowaste composition from villages, towns and cities of Maharashtra. Biowaste fraction of municipal solid waste assessed at waste collection points. Biochemical methane potential (BMP) of major municipal biowaste streams. Effects of seasonal variations in the composition of these biowastes on BMP. Abstract: Anaerobic digestion (AD) of biowaste can generate biogas with methane (CH4 ) as energy source and contribute to sustainable municipal solid waste management in India. Characteristic municipal biowastes sampled seasonally from household, fruit and vegetable market and agricultural waste collection points in villages, towns and cities in Maharashtra were analysed to assess the potential as substrate for AD. The mean biochemical methane potential (BMP, at 37 °C) across seasons and community sizes was between 200–260, 175–240 and 101–286 NLCH4  kgvs −1 for household, market and agricultural biowaste, respectively. CH4 yields were comparable in villages, towns and cities. Seasonal variations in CH4 yields were observed for market and agricultural biowaste with highest values during pre-monsoon season. Results underpin that municipal biowaste is a suitable substrate for AD in India. However, low purity of available biowaste resulted in lower CH4 yields compared to recent studies using source-segregated biowaste.